Hermeneutika sebagai Metode Ilmu Kemanusiaan - I Ketut Wisarja (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2003)
Since Auguste Comte periode, natural science dominated the development of scientific methodes and even used in social, humanities, and cultural science. In the end of 19th century, any consciusness of unsufficient method of natural science was begun. Wilhelm Dilthey (1833-1911) started using new way. He was a person who attempted to differ geisteswissenschaft and naturalwissenschaft to make different method. He introduced hermeneutics as an alternative method for humanities.